2008
DOI: 10.1093/bja/aem409
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a minimally invasive uncalibrated cardiac output monitoring system (Flotrac™/Vigileo™) in haemodynamically unstable patients †

Abstract: Background. Early haemodynamic assessment is of particular importance in the evaluation of haemodynamically compromised patients, but is often precluded by the invasiveness and complexity of the established cardiac output (CO) monitoring techniques. The FloTrac TM /Vigileo TM system allows minimally invasive CO determination based on the arterial pressure waveform derived from any standard arterial catheter, and the algorithm underlying CO calculation was recently modified to allow a more precise estimate of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 13 publications
6
70
1
1
Order By: Relevance
“…While similar observations were reported with earlier generations of the device [3], recent reports on newer software generations Flotrac™/ Vigileo™ (3.01) have reported more accurate measurements of cardiac output and stroke volume in patients with sepsis [4]. Our patient differs from this cohort in several ways.…”
Section: Discussionsupporting
confidence: 84%
“…While similar observations were reported with earlier generations of the device [3], recent reports on newer software generations Flotrac™/ Vigileo™ (3.01) have reported more accurate measurements of cardiac output and stroke volume in patients with sepsis [4]. Our patient differs from this cohort in several ways.…”
Section: Discussionsupporting
confidence: 84%
“…However, our data can be compared with a recent review and meta-analysis of studies on the accuracy and precision of the FloTrac by Mayer et al 91 These authors found a percentage error of 44% for earlier versions of the device and 30% for later versions (v1.07ϩ), but this review excluded studies involving patients with hemodynamic instability or vasodilatory states, thus restricting their analysis to cardiac surgery alone. Subanalysis of our data for studies on the FloTrac found a percentage error of 47.3% for earlier versions and 44.7% for v1.07ϩ, but the latter contained two studies in septic or critically ill patients, 99,100 where high cardiac outputs and hemodynamic instability present greater challenges to the accuracy and precision of a measurement device. Therefore these results for the FloTrac still compared well with the other methods we have surveyed in the current review.…”
Section: Discussionmentioning
confidence: 91%
“…Critchley and Critchley proposed that the acceptance of any method of determination of CO should be judged against the accuracy of the reference method which is till date considered being the ITD method obtained by PAC [22]. Since the measurement of this physiological variable generally lacks precision, error of +10-20% are common even for the reference method.…”
Section: Citationmentioning
confidence: 99%
“…Similar alterations were also observed when the arterial pressure waveform is changed as in patients with aortic insufficiency and in patients on IABP. Many other studies involving other different subsets of patients have produced inconsistent results when the CO was measured with thermodilution and pulse contour analysis techniques [4][5][6][14][15][16]22,[28][29][30][31][32]. Thus, although FloTrac method has many potential advantages including non-invasiveness, simplicity, no need for external calibration and minimal operator intervention, it still has many limitations in a variety of situations.…”
Section: Citationmentioning
confidence: 99%